Madhuca Longifolia (Sapotaceae): A Review of its Phytochemical and Pharmacological Profile - N. DEVI; R. SANGEETHA (International Journal of Pharma and Bio Sciences, 2016)
Herbal medicine is still the mainstay of about 75 – 80% of the world’s population in the developing countries for primary health care. Madhuca longifolia (Mahua) Syn. Madhuca indica (Sapotaceae) commonly known as Butter nut tree is an economic plant growing throughout the subtropical region of the Indo – Pak subcontinent. Extensive studies show the presence of secondary metabolites like sapogenins, triterpenoids, saponins, flavonoids and glycosides. Conventionally, it has been used to treat infections, wounds, rheumatism, heart disease, diabetes and many other disorders. Experimental studies have demonstrated that Mahua exhibits antimicrobial, antioxidant, antiinflammatory, antiulcer, cardioprotective, anticarcinogenic, immunomodulant and hypoglycaemic properties. The outcome of these studies have emphasized the existing pharmacological profile of Mahua and provided a convincing support to its future clinical use in modern medicine.